Human-AI teams—Challenges for a team-centered AI at work - Hagemann, Vera; Rieth, Michèle; Suresh, Amrita; Kirchner, Frank (Frontiers in Artificial Intelligence, 2023)
As part of the Special Issue topic "Human-Centered AI at Work: Common Ground in Theories and Methods", we present a perspective article that looks at human-AI teamwork from a team-centered AI perspective, i.e. we highlight important design aspects that the technology needs to fulfil in order to be accepted by humans and to be fully utilized in the role of a team member in teamwork. Drawing from the model of an idealized teamwork process, we discuss the teamwork requirements for successful human-AI teaming in interdependent and complex work domains, including e.g., responsiveness, situation awareness, and flexible decision-making. We emphasize the need for teamcentered AI that aligns goals, communication, and decision making with humans, and outline the requirements for such team-centered AI from a technical perspective, such as cognitive competence, reinforcement learning, and semantic communication. In doing so, we highlight the challenges and open questions associated with its implementation that need to be solved in order to enable effective human-AI teaming.